Pengaruh Pelatihan, Disiplin, dan Pengawasan terhadap Kinerja Pegawai Badan Usaha Milik Desa (BUMDes) di Kota Ambon - Muhlisa, Arita; Pentury, G. M.; Leuhery, F. (Universitas Batanghari, 2024)
Ambon City consists of 30 villages and 20 sub-districts. In 2018 there are 14 villages established Badan Usaha Milik Desa (BUMDes). BUMDes is one of the business units in the village is expected to be able to increase community efforts in managing village potential in Ambon City. Reality, BUMDes in Ambon City has some issues, including insufficient andÂ subpar of human resources. Based on these issues, the research aims to determine and analyze the influence of training, discipline and supervision on the performance of Ambon City BUMDes employees. The research method used is quantitative research. Data was obtained through interviews, observations and questionnaires. Data analysis using linear regression analysis using SPSS 26 software. The sample used was 40 employees in BUMDes, Ambon City. The research results show that training, discipline and supervision variables influence the performance of Ambon City BUMDes employees. It is hoped that the implications of this research will serve as material for consideration and evaluation to improve and enhance the performance of Ambon City BUMDes employeesÂ